Microglia-mediated inflammatory destruction of neuro-cardiovascular dysfunction after stroke - Deng, Jiahong; Chen, Chenghan; Xue, Shuaishuai; Su, Daoqing; Poon, Wai Sang; Hou, Honghao; Wang, Jun (Frontiers in Cellular Neuroscience, 2023)
Stroke, a serious systemic inflammatory disease, features neurological deficits and cardiovascular dysfunction. Neuroinflammation is characterized by the activation of microglia after stroke, which disrupts the cardiovascular-related neural network and the blood–brain barrier. Neural networks activate the autonomic nervous system to regulate the cardiac and blood vessels. Increased permeability of the blood–brain barrier and the lymphatic pathways promote the transfer of the central immune components to the peripheral immune organs and the recruitment of specific immune cells or cytokines, produced by the peripheral immune system, and thus modulate microglia in the brain. In addition, the spleen will also be stimulated by central inflammation to further mobilize the peripheral immune system. Both NK cells and Treg cells will be generated to enter the central nervous system to suppress further inflammation, while activated monocytes infiltrate the myocardium and cause cardiovascular dysfunction. In this review, we will focus on microglia-mediated inflammation in neural networks that result in cardiovascular dysfunction. Furthermore, we will discuss neuroimmune regulation in the central–peripheral crosstalk, in which the spleen is a vital part. Hopefully, this will benefit in anchoring another therapeutic target for neuro-cardiovascular dysfunction.